Increased nutrient supply to the Southern Ocean during the Holocene and its implications for the pre-industrial atmospheric CO2 rise - Studer, Anja; Lippold, Jörg (Nature geoscience, 2018)
The amount of nitrate in the surface of the Southern Ocean has increased during the Holocene, weakening the biological pump and potentially contributing to the rise in atmospheric CO2 concentrations.
Gesehen am 23.04.2019
Im Titel ist „2“ tiefgestellt